The Influence of Farmer's Dependency and Power to Performance - Hadi, Diandra Adelina; Purwanegara, Mustika Sufiati (Journal of Business and Management, 2016)
Abstract. This research examines the influence of dependency and power to performance in the agriculture sector, from the farmer’s point of view. Indonesia’s agriculture sector contributes to 33% of the GDP and absorbs 41 million farmers; most of them still live in poverty. If the performance can be increased, it is hoped that the money generated and the farmer’s welfare can be increased too. Keywords: buyer-supplier relationship, farmers, dependency, power, performance